Immunohistochemical Analysis of Cerebral Intraparenchymal Choroid Plexus Tumor: Case Report - Katoh, Masahito; Sawamura, Yutaka; Tanaka, Shinya; Fujimaki, Takamitsu; Hirose, Shigehisa; Aida, Toshimitsu (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background It is very rare for a choroid plexus tumor to occur intraparenchymally in the absence of a relation to the choroid plexus.Clinical Presentation A case of cerebral intraparenchymal choroid plexus tumor in a 30-year-old woman presenting with left hemiparesis is described. Brain magnetic resonance imaging depicted a large cystic mass in the right frontal lobe. Tumor resection was performed by right frontal craniotomy. No connection with the choroid plexus was observed during the operation. Histologically, the tumor exhibited a glandular structure with a papillary pattern suggesting a neoplasm of epithelial origin. Immunohistochemical analyses revealed the tumor as an atypical choroid plexus papilloma.Conclusion Immunohistochemical findings, especially regarding Kir7.1, are very important for the differential diagnosis of cerebral intraparenchymal choroid plexus tumors from metastatic tumors. The present case reveals that an atypical choroid plexus papilloma can occur intraparenchymally without an association with the choroid plexus. Intraparenchymal atypical choroid plexus papillomas may have previously been diagnosed incorrectly as metastatic adenocarcinomas of unknown origin.
Keywords: intraparenchymal; choroid plexus tumor; Kir7.1